Solution-processed star-shaped oligomers in normal and inverted organic solar cells - Trukhanov, Vasily A.; Mannanov, A. L.; Burgués-Ceballos, Ignasi; Savva, Achilleas; Solodukhin, Alexander N.; Luponosov, Yuriy N.; Ponomarenko, Sergey; Paraschuk, Dmitry Yu; Choulis, Stelios A. (My University, 2016)
The performance of three different star-shaped oligomers (SSOs) as electron donor materials for organic solar cells is investigated. These promising donor components are blended with [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) fullerene acceptor and solution-processed normal and inverted organic solar cells are fabricated. These SSOs are based on a triphenylamine core and differ in the solubilizing groups and the oligothiophene arm length. We have found that the power conversion efficiency (PCE) is by 10-60% higher in the normal structure, mainly due to an enhanced open-circuit voltage and fill factor. The observed difference in device performance can be assigned partly to the lower leakage currents. By using contact angle measurements and atomic-force microscopy studies, we estimate the degree of vertical phase separation in bulk heterojunctions. The latter has a good correlation to the corresponding photocurrent differences obtained in the normal and inverted structure devices.
Keywords: Normal and inverted architecture; Small-molecule organic solar cells; Star-shaped oligomers